Deconstructing Beauty: A Critical Discourse Analysis of Why You Think You’re Ugly by Melissa Butler - Lestari, Kurnia; Sartika, Delita; Hustarna, Hustarna (Langue (Journal of Language and Education), 2025)
One of the most important areas of focus in English instruction, especially at higher levels, is the ability to interpret and assess the underlying meanings of written and spoken texts, particularly those that deal with social issues. To help students develop their critical thinking and discourse analysis skills, teachers can include real-world materials like TED Talks in English language instruction. Through a critical discourse lens, this study examines how Melissa Butler's TED Talk, Why You Think You're Ugly, questions prevailing beauty standards. The study focuses on the descriptive and explanatory elements of Fairclough's framework while analyzing the textual elements and social contexts of Butler's discourse. Data were collected from the video transcript and categorized using Hall's beauty framework to emphasize themes such as body size, face traits, skin tone, and hair texture. The findings showed that Butler used rhetorical strategies and personal storytelling to critique linear beauty norms, expose the emotional toll of conformity, and advocate for a more inclusive vision of beauty. Her discourse emerged as a counter-narrative, resisting Eurocentric ideals and affirming cultural identity and self-acceptance. Ultimately, the study underscores the role of discourse in shaping social perceptions and supports the ongoing movement toward equity in beauty representation.